2014
DOI: 10.1016/j.ijid.2014.03.790
|View full text |Cite
|
Sign up to set email alerts
|

Bovine tuberculosis surveillance system evaluation - Greater-Accra Region, Ghana, 2011

Abstract: Background: Bovine tuberculosis (BTB) is caused by Mycobacterium bovis. Developed countries have succeeded to control BTB infections and reduced its transmission to humans through the enforcement of meat inspection laws, test and slaughter/segregation of positive reactors, and milk pasteurisation. This was paralleled by a concomitant decrease in human tuberculosis infections (HTBI) from 5%-20% to 0.5%-1% in the past five decades. In developing countries, an estimated 10-15% of HTBI are attributed to M. bovis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The system was partially meeting its intended objectives. Some surveillance system evaluations conducted in Ghana for diseases have also concluded that the systems evaluated were not fully achieving their intended objectives [ [16] , [17] , [18] , [19] , [20] ]. A study in Brazil which used a different evaluation method to evaluate the Food and Nutrition Surveillance System (SISVAN) of the State of Minas Gerais, Brazil also concluded that the system was not being used to its full potential and that the data generated from the system was not used for planning, management and evaluation of nutrition services [34].…”
Section: Discussionmentioning
confidence: 99%
“…The system was partially meeting its intended objectives. Some surveillance system evaluations conducted in Ghana for diseases have also concluded that the systems evaluated were not fully achieving their intended objectives [ [16] , [17] , [18] , [19] , [20] ]. A study in Brazil which used a different evaluation method to evaluate the Food and Nutrition Surveillance System (SISVAN) of the State of Minas Gerais, Brazil also concluded that the system was not being used to its full potential and that the data generated from the system was not used for planning, management and evaluation of nutrition services [34].…”
Section: Discussionmentioning
confidence: 99%